Efficacy and Safety of Antibiotic Therapy in Early Cutaneous Lyme Borreliosis: A Network Meta-analysis - Torbahn, Gabriel; Hofmann, Heidelore; Rücker, Gerta; Bischoff, Karin; Freitag, Michael H; Dersch, Rick; Fingerle, Volker; Motschall, Edith; Meerpohl, Jörg; Schmucker, Christine (JAMA Dermatology, 2018)
Importance Controversies about the choice of antibiotic agent and treatment modality exist in the management of erythema migrans in early cutaneous Lyme borreliosis (LB). Objective To conduct a network meta-analysis (NMA) of all randomized clinical trials on various antibiotic agents and treatment modalities in early cutaneous LB. Data Sources Electronic searches in MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials were conducted from inception until July 2017. The reference lists of the included studies were hand searched, authors were contacted, and ongoing trials were searched at ClinicalTrials.gov. Study Selection One reviewer screened the titles and abstracts of the 9975 reports identified by the electronic searches. Full-text copies of 161 potentially relevant articles were obtained, and 2 reviewers independently assessed those articles for inclusion. Adults with a physician-confirmed early localized skin infection who were treated with antibiotics of any dose or duration were included. Data Extraction and Synthesis Two reviewers independently extracted data on study, patient, and intervention characteristics. Network meta-analyses on treatment effects and adverse outcomes were calculated with a frequentist approach using the R package netmeta. The Grading of Recommendations Assessment, Development and Evaluation guidance for NMA was used to assess the certainty of evidence. Main Outcomes and Measures Treatment effects for response to treatment (resolution of symptoms) and treatment-related adverse events. Results Overall, 19 studies (2532 patients) were included. The mean patient age ranged between 37 and 56 years, and the percentage of female patients ranged from 36% to 60%. The antibiotics investigated were doxycycline, cefuroxime axetil, ceftriaxone, amoxicillin, azithromycin, penicillin V, and minocycline. Pooled effect sizes from NMAs did not suggest any significant differences in treatment response by antibiotic agent (eg, amoxicillin vs doxycycline odds ratio, 1.26; 95% CI, 0.41-3.87), dose, or duration (eg, doxycycline, 200 mg/d for 3 weeks, vs doxycycline, 200 mg/d for 2 weeks, odds ratio, 1.28; 95% CI, 0.49-3.34). Treatment failures were rare at both 2 months (4%; 95% CI, 2%-5%) and 12 months (2%, 95% CI, 1%-3%) after treatment initiation. There were also no differences in the effect sizes among antibiotic agents and treatment modalities for treatment-related adverse outcomes, which were generally mild to moderate. Certainty of evidence was categorized as low and very low mostly because of imprecision, indirectness, and study limitations (high risk of bias) of the included studies. Conclusions and Relevance This NMA suggests that neither the antibiotic agent nor treatment modality contributed to comparative effectiveness or drug-related adverse outcomes. This finding is relevant for physicians treating patients with LB and for patient decision makin